Renal secretion of hydrochlorothiazide involves organic anion transporter 1/3, organic cation transporter 2, and multidrug and toxin extrusion protein 2-K - Yin, Jia (Am J Physiol Renal Physiol, 2019)
Hydrochlorothiazide (HCTZ) is the most widely used thiazide diuretic for the treatment of hypertension either alone or in combination with other antihypertensives. HCTZ is mainly cleared by the kidney via tubular secretion, but the underlying molecular mechanisms are unclear. Using cells stably expressing major renal organic anion and cation transporters [human organic anion transporter 1 (hOAT1), human organic anion transporter 3 (hOAT3), human organic cation transporter 2 (hOCT2), human multidrug and toxin extrusion 1 (hMATE1), and human multidrug and toxin extrusion 2-K (hMATE2-K)], we found that HCTZ interacted with both organic cation and anion transporters. Uptake experiments further showed that HCTZ is transported by hOAT1, hOAT3, hOCT2, and hMATE2-K but not by hMATE1. Detailed kinetic analysis coupled with quantification of membrane transporter proteins by targeted proteomics revealed that HCTZ is an excellent substrate for hOAT1 and hOAT3. The apparent affinities (K(m)) for hOAT1 and hOAT3 were 112 ± 8 and 134 ± 13 μM, respectively, and the calculated turnover numbers (k(cat)) were 2.48 and 0.79 s(−1), respectively. On the other hand, hOCT2 and hMATE2-K showed much lower affinity for HCTZ. The calculated transport efficiency (k(cat)/K(m)) at the single transporter level followed the rank order of hOAT1> hOAT3 > hOCT2 and hMATE2-K, suggesting a major role of organic anion transporters in tubular secretion of HCTZ. In vitro inhibition experiments further suggested that HCTZ is not a clinically relevant inhibitor for hOAT1 or hOAT3. However, strong in vivo inhibitors of hOAT1/3 may alter renal secretion of HCTZ. Together, our study elucidated the molecular mechanisms underlying renal handling of HCTZ and revealed potential pathways involved in the disposition and drug-drug interactions for this important antihypertensive drug in the kidney.